Effects of ZnO addition on thermal properties, degradation and biocompatibility of P45Mg24Ca16Na(15−x)Znx glasses - Wang, Yunqi; Zhu, Chenkai; Parsons, Andrew; Rudd, Chris; Ahmed, Ifty; Sharmin, Nusrat (Walter de Gruyter GmbH, 2019)
Four phosphate-based glass formulations in the system P45Mg24Ca16Na(15-x)Znx, referred to as P45Znx (x = 0, 5, 10 and 15 mol%), were prepared using a melt quenching process. The effect of ZnO addition on density, molar volume, thermal properties and degradation rates were studied. An increase in the glass transition, crystallisation, melting and liquidus temperatures were seen when replacing Na2O with ZnO. The molar volume of the bulk glasses was seen to decrease with increasing ZnO content. The dissolution rate of the zinc-free glass was 2.48 × 10-8 kg m-2 s-1 and addition of 5 mol% ZnO resulted in a reduction of the dissolution rate to 1.68 × 10-8 kg m-2 s-1. However, further addition of ZnO from 5 mol% to 15 mol% increased the dissolution rate of the glass system. The glasses were deliberately crystallised and XRD studies identified the Z n2P2O7 phase for glass code P45Zn5, and Zn(PO3)2 phase for P45Zn10 and P45Zn15 glasses. Cyto-compatibility studies were conducted using MG63 cells for 14 days. An overall increase in the metabolic activity and DNA concentration of cells was seen from day 1 to day 14 for all glass formulations investigated. However, increasing ZnO content from 0 to 15 mol% seemed to have a negative effect on the cellular activity. Interestingly, a remarkably higher ALP activity was seen at day 14 for glass codes P45Zn5 and P45Zn10 in comparison with the TCP control and the P45Zn0 glass.